INCREASING STUDENTSâ€™ WRITING ABILITY BY USING THE MAGIC BACK AND FORTH MEDIA AT CLASS IX-B SMPN 3 X KOTO SINGKARAK - Karyawetti, Yunita (English Department FBS UNP, 2011)
The aim of this research is to find out whether the studentsâ€™ ability in writing procedure text can be increased by using the â€˜Magic Back and Forthâ€™ Media or not. So, the title of this Classroom Action Research is â€œIncreasing Studentsâ€™ Writing Ability by Using the Magic Back and Forth Media at Class IX-B SMPN 3 X Koto Singkarakâ€. This research is Classroom Action Research (CAR) and the subject of the research is 29 students of class IX-B. The research was conducted in two cycles which there were four steps for each cycle; planning, acting, observing and reflecting. The data were collected through observation, questionaire, and conducting the test after implementing each cycle. The results of each cycle showed that the studentsâ€™ writing ability can be increased by Using the â€˜Magic Back and Forthâ€™ Media. It can be seen from the result of the testsâ€™; 71, 9 at cycle 1 and 77,7 at cycle 2. Key Words: writing ability, procedure text, magic back and forth media.